Pendidikan Seksual Bagi Anak Berkebutuhan Khusus: Sebuah Review Literatur Sistematis - Handayani, Endang Sri; Zulpiani, Mardhatillah; Rahmahtrisilvia, Rahmahtrisilvia; Budi, Setia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to systematically review various approaches and the effectiveness of sex education implementation for children with special needs in Indonesia. The research method employs a literature study by examining relevant scientific articles published regarding sex education for children with special needs. The data analysis technique used is thematic analysis. The analysis results indicate that sexual education interventions, such as Moduseksi psychoeducation, sociodrama methods, and the use of song media, significantly improve children's knowledge and understanding of sexual concepts, body boundaries, and efforts to prevent sexual abuse. However, challenges remain in the limitations of materials, parental resistance, and the constraints of learning methods that fit the children's characteristics. This research emphasizes that sexual education must be packaged in an engaging way, be easy to understand, tailored to the children's needs, and involve the active participation of parents, teachers, and professionals. Sexual education provided from an early age has been proven to positively contribute to children's readiness to face biological and social changes, as well as strengthen protection against the potential of sexual violence. Therefore, there is a need for the development of innovative methods and materials to support the effectiveness of sexual education for special needs children sustainably.